The phylogeny of Seseli (Apiaceae, Apioideae): insights from molecular and morphological data - Jing Cai; Huan-Huan Qin; Jia-Qing Lei; Chang-Kun Liu; Xing-Jin He; Song-Dong Zhou (BMC Plant Biology, 2022)
Abstract Background The genus Seseli L., which consists of 125–140 species distributed in the Old World from western Europe and northwestern Africa to China and Japan, is one of the largest and most taxonomically difficult genera of Apiaceae Lindl. Although several previous studies have been conducted on Seseli based on limited morphological characteristics and molecular fragments, a robust and comprehensive phylogeny of Seseli remains elusive. Plastomes provide abundant genetic information and have been widely used in studying plant phylogeny and evolution. Consequently, we newly generated the complete plastomes of eleven Seseli taxa. We combined plastome data and morphological characteristics to investigate the phylogeny of Seseli. Results In our study, we observed that the genome length, gene numbers, IR/SC borders, and repeat composition of the eleven Seseli plastomes were variable. Several appropriate mutation hotspot regions may be developed as candidate DNA barcodes for evolution, phylogeny, and species identification of Seseli. The phylogenetic results identified that Seseli was not a monophyletic group. Moreover, the eleven newly sequenced Seseli taxa did not cluster with S. tortuosum (the type species of Seseli, belonging to the tribe Selineae), where S. delavayi clustered with Eriocycla belonging to the tribe Echinophoreae and the other ten belonged to Selineae. The comparative plastome and morphological characteristics analyses confirmed the reliability of the phylogenetic analyses and implied the complex evolution of Seseli. Conclusion Combining molecular and morphological data is efficient and useful for studying the phylogeny of Seseli. We suggest that “a narrow sense” of Seseli will be meaningful for further study and the current taxonomic system of Seseli needs to be revised. In summary, our study can provide new insights into the phylogenetic relationships and taxonomic framework of Seseli.